YTHDF2 mediates the protective effects of MG53 on myocardial infarction injury via recognizing the m6A modification of MG53 - Zhaojie Li; Kai Li; Jianqiang Zhao (Journal of Cardiothoracic Surgery)
Abstract Introduction High levels of MG53 may attenuate the damage from myocardial infarction (MI). Furthermore, N6-methyl-adenosine (m6A) methylation is a mode of RNA modification that influences mRNA functions. Whether m6A modification on MG53 exerts a protective role on myocardial injury remains largely unknown. Materials and methods We established hypoxia/reoxygenation (H/R) H9c2 cell and myocardial ischemia reperfusion (I/R) rat models. MG53 expression was detected using RT-qPCR, and its m6A levels were measured using Me-RIP. The relationship between MG53 and YTHDF2 was evaluated using RNA immunoprecipitation, FISH and immunofluorescence assay, and luciferase reporter assay. MI area of rats was determined using TTC staining. Cell apoptosis was assessed by flow cytometry and TUNEL assay. Results The m6A levels of MG53 were increased in H/R-induced H9c2 cells and the myocardium of I/R rats. Moreover, knockdown of YTHDF2 recognized the m6A modification of MG53 and enhanced MG53 stability. Overexpression of MG53 inhibited apoptosis of H/R-treated H9c2 cells, which was reversed by YTHDF2, while downregulation of MG53 m6A methylation caused by METTL3 knockdown further abrogated the effect induced by YTHDF2. Additionally, MG53 attenuated MI and apoptosis in I/R rats, which were rescued by YTHDF2. Conclusion YTHDF2 hinders the protective effect of MG53 on MI by recognizing the m6A modification of MG53.